Efeito do biofertilizante no desenvolvimento de porta-enxertos de citros e na indução de resistência à gomose de Phytophthora - Faldoni, Luciana (Universidade Federal de São Carlos, 2011)
Among the problems faced by the plant citrus sector, stands out of Phytophthora gummosis, which affects all stages of plant development. For disease control chemicals are used, but seeking a more sustainable agriculture, alternative control techniques have been adopted, including the use of biofertilizers. Therefore, this work aimed to: (i) to produce a biofertilizer from the anaerobic digestion of cattle manure with crushed sugar cane, (ii) determine the microbial diversity present in compost, (iii) verify the effect of compound on mycelial growth of Phytophthora parasitica, (iv) to observe its effect on plant growth, and finally (v) evaluate its effect on induction of resistance to the pathogen. It was found that in the period between 25 to 35 days of production of biofertilizer met the highest microbial population, specially composed by Bacillus spp. and other bacteria. The biofertilizer at concentrations of 10 and 20% favored the vegetative growth of rootstock Poncirus trifoliata, Rangpur, sunki and sour oranges, and the concentration of 20% in orange plants Caipira favored disease control. The genes encoding β 0.1-3-glucanase (PR-2), chalcone synthase (CHS) and lipoxygenase (LOX) were activated in plants treated with biofertilizer and inoculated into susceptible rootstock, the biofertilizer was able to activate genes encoding chitinase (CHI) and chalcone synthase (CHS), possibly involved with the resistance of citrus plants to P. Parasitica.
Effect of the development of the biofertilizer rootsocks citrus and induction of resistance buds of Phytophthora
Keywords: Agricultura orgânica; Expressão gênica; Gomose; Agricultura orgânica; Gene expression; Gummosis; Organic agriculture; CIENCIAS AGRARIAS